Handbook of physical-chemical properties and environmental fate for organic chemicals on CD-ROM - Mackay, Donald (Boca Raton, Fla. Taylor & Francis, 2006)
The handbook contains physical-chemical property data from peer-reviewed journals and other valuable sources on over 1200 chemicals of environmental concern. The handbook contains new data on the temperature dependence of selected physical-chemical properties, which allows scientists and engineers to perform better chemical assessments for climatic conditions outside the 20-25-degree range for which property values are generally reported
Title from container
Acrobat reader 7.x installation included on this CD-ROM
System requirements: 16 MB RAM; 15 MB available disk space; CD-ROM drive (4X); SVGA monitor at 800x600, 256 colors; Microsoft windows 2000 or XP must be installed on the host computer; Adobe acrobat reader 5.x or higher (Acrobat reader 7.x installation included on this
Keywords: Organic compounds -- Environmental aspects; Environmental chemistrya; Organic compounds -- Properties